Circulating cytokines and angiogenic factors based signature associated with the relative dose intensity during treatment in patients with advanced hepatocellular carcinoma receiving lenvatinib. (May 2020) - Ono, Atsushi; Aikata, Hiroshi; Yamauchi, Masami; Kodama, Kenichiro; Ohishi, Waka; Kishi, Takeshi; Ohya, Kazuki; Teraoka, Yuji; Osawa, Mitsutaka; Fujino, Hatsue; Nakahara, Takashi; Murakami, Eisuke; et al.
Background: Although lenvatinib was recently approved for treatment of advanced unresectable hepatocellular carcinoma (HCC) based on the phase III REFLECT trial, no biomarkers for management of lenvatinib treatment have been established. The aim of this study is to identify predictive biomarkers for the management of lenvatinib treatment in advanced HCC patients. Methods: A total of 41 patients with advanced HCC were enrolled in this retrospective study. Serum levels of 22 circulating cytokines and angiogenic factors (CAFs) were measured by multiplex Luminex assay. Profiles of CAFs, clinical chemistry/hematology parameters, and clinical background were evaluated to explore biomarkers associated with clinical outcomes. Results: Relative dose intensity (RDI) decreased significantly between weeks 1–2 and 3–4 ( p < 0.001), and RDI during weeks 3–4 was a prominent indicator of progression-free survival (PFS). A signature based on baseline serum levels of nine CAFs associated with low RDI was identified. In a multivariate Cox regression analysis, patients with a favorable 9-CAFs signature [hazard ratio (HR) 0.42, 95% confidence interval (CI) 0.18–0.96, p = 0.040] had lower risk, and Child-Pugh grade B (HR 1.6, 95% CI 1.1–8.3, p = 0.026) and presence of macrovascular invasion (MVI; HR 2.9, 95% CI 1.0–8.3, p = 0.045) had higher risk of shorter PFS. Conclusion: This study demonstrates that RDI is an important predictive factor for longer PFS during lenvatinib treatment. In this hypothesis-generating exploratory analysis, we report that a CAF-signature associated with adverse events and RDI could predict PFS, which might contribute to improved management of lenvatinib treatment in HCC patients.